Outcome of Patients with Spontaneous Intracerebral Hemorrhage at Tertiary Care Hospital in Nepal - Kafle, Dilli Ram (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 35-43 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8803